IDEOLOGY AND FICTION (“DIE HARD”) - KERŠYTĖ, NIJOLĖ (Politologija, 2013)
The first, theoretical, part of this article presents a brief survey of the Marxist and neo-Marxist theory concerning ideology. Starting from the conception of ideology as a false image of the world, this tradition has evolved towards the definition of ideology as a set of symbolic and discursive structures. This change, which is performed in Althusser’s works, allows to compare the Althusserian neo-Marxist conception of ideology with Greimas’ structural semiotics, which offers methodological tools for the analysis of ideological manifestations in narrative fiction.The second part is devoted to a semiotic study of the action film “Die Hard” with the purpose of disclosing the organisation of its ideological dimension. In this film, ideological values are mostly conveyed by the way how narrative roles of individual characters are constructed, by the form attributed to collective identities, and by the relations of both to space. The analysis shows that four different ideologies intersect in this cinematographic narration.